Effect of potential screening on the H2 autoionizing states (2017)
ABSTRACT: We study the behavior of autoionizing states of the hydrogen molecule subject to screened Coulomb interactions using an ab initio Feshbach configuration interaction method. Special attention is given to the algorithms developed for the evaluation of (i) screened molecular orbitals expressed in terms of one-center expansions using B-spline polynomial basis functions and (ii) screened two-electron integrals between configurations expressed in terms of such molecular orbitals, by solving the screened Poisson equation. As an illustration of the method we focus on the lowest Feshbach resonance of the Q1 1+g series of doubly excited states of H2, which lies between the first H2 + (1sσg) and the second H2 + (2pσu) ionization thresholds. We show that Coulomb screening in the electron-proton interaction and between electrons may significantly alter the resonance position and autoionizing decay as a function of internuclear distance. In general, screening increases the resonance lifetime. However, when electron-proton screening dominates over electron-electron screening, we find that the Q1 resonance acquires a pronounced shape-resonance character at internuclear distances where the resonance approaches the lower ionization threshold, thus leading to a pronounced decrease of its lifetime.